Analisa Pengaruh Penggunaan Gadget Terhadap Nilai Akhir Siswa SMA Secara Umum Menggunakan Metode Data Mining (Decision Tree) - Raja Simarmata; Yusran Timur Samuel (TeIKa, 2021)
The rapid development of technology is currently used by all ages. The use of gadgets among teenagers today is really busy and will certainly affect their learning attitudes and their final grades. Data mining is a method of processing large amounts of data to find information from that data. ID3 is a data mining algorithm that uses the entropy method. The result of this study is that gadgets do not affect the final grades of high school students in general.